An Economic Perspective on Policies to Save the Vaquita: Conservation Actions, Wildlife Trafficking, and the Structure of Incentives - Sanjurjo-Rivera, Enrique; Mesnick, Sarah L.; Ávila-Forcada, Sara; Poindexter, Oriana; Lent, Rebecca; Felbab-Brown, Vanda; Cisneros-Montemayor, Andrés M.; Squires, Dale; Sumaila, U. Rashid; Munro, Gordon; Ortiz-Rodriguez, Rafael; Rodriguez, Ramses; et al. (Frontiers in Marine Science, 2021)
The Upper Gulf of California is a diverse and highly productive ecosystem supporting some of the most important fisheries in Mexico, yet a history of weak fisheries management and illegal fishing threaten the area’s biodiversity and undermine human well-being in the communities along its shores. The vaquita (Phocoena sinus) is endemic to these waters and is on the brink of extinction due to incidental entanglement in gillnets used by small-scale fishers. The resurgence of an illegal gillnet fishery for totoaba (Totoaba macdonaldi), whose swim bladders are highly prized in Hong Kong and continental China, has accelerated the steep decline of the vaquita population. Vaquita is one of a growing number of cases linking illegal wildlife trade, organized crime, and biodiversity decline. This paper provides a summary of key reflections of a panel of fisheries economists gathered at the ninth forum of the North American Association of Fisheries Economists (NAAFE) to evaluate the policies implemented in the Upper Gulf through an economic lens and updated to reflect more recent developments. The panel recognized that poor fisheries management, lack of effective enforcement, distant demand for an illegal product, corruption, and few viable economic alternatives confound efforts to address vaquita bycatch. The complexity of these problems requires a holistic, multidisciplinary approach, combining top-down, direct regulation and bottom-up, participatory and incentive-based instruments. Addressing chronic deficiencies in enforcement, particularly in the very small area where the remaining vaquitas are found, is crucial to prevent imminent extinction. Equally crucial are sustained actions to support legal fishers able to make a good living – with a direct stake in healthy marine ecosystems – as key components of policies to address bycatch and reduce wildlife trafficking. The situation in the Upper Gulf of California is dire, yet similar threats to other marine mammals and wildlife trafficked species may benefit from the experience of the vaquita.